2003
DOI: 10.1023/a:1027467617722
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Atrial fibrillation (AF) is the most common complication of coronary artery bypass grafting (CABG), usually occurring on the second or third post-operative day. Post-operative AF is associated with prolonged hospital stay and increased costs. In several randomized trials, prophylactic oral beta-blocker reduced the incidence of post-operative AF. Theoretically, intravenous beta-blocker regimen with its rapid onset of action and ease of dose titration should be more efficacious than oral beta-blocker. We conduct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…It should be mentioned that patients at risk to develop complications associated with IV metoprolol were excluded. Also, Maniar et al randomized 47 patients for elective CABG to receive either esmolol IV or standard oral β-blocker (propanolol/metoprolol) [31]. Esmolol was given within 6 to 18 hours of arrival to recovery room, continued for up to 24 hours and then these patients transitioned to oral β-blocker.…”
Section: Pharmacologic Prophylaxis For Postoperative Atrial Fibrillationmentioning
confidence: 99%
“…It should be mentioned that patients at risk to develop complications associated with IV metoprolol were excluded. Also, Maniar et al randomized 47 patients for elective CABG to receive either esmolol IV or standard oral β-blocker (propanolol/metoprolol) [31]. Esmolol was given within 6 to 18 hours of arrival to recovery room, continued for up to 24 hours and then these patients transitioned to oral β-blocker.…”
Section: Pharmacologic Prophylaxis For Postoperative Atrial Fibrillationmentioning
confidence: 99%
“…could not report any advantage with intravenous esmolol over oral usage of metoprolol, they reported a concern of higher incidence of hemodynamic compromise with the use of esmolol. [ 29 ] A study has reported better results in controlling postoperative atrial fibrillation with carvedilol when its prophylactic use was compared to metoprolol. [ 30 ] Prophylactic use of amiodarone has also shown to reduce postoperative atrial fibrillation significantly.…”
Section: Discussionmentioning
confidence: 99%
“…In the European Society of Cardiothoracic Surgery 2006 guidelines [104] the perioperative use of beta blockers is recommended as the first choice in all patients undergoing cardiac surgery, unless otherwise contraindicated. Intravenous administration is more effective in some series [105] but the tolerance is poor due to the development of side effects [106]. Different beta blockers have been compared.…”
Section: Supraventricular Tachyarrhythmiasmentioning
confidence: 99%